Perbandingan Skala Nyeri pada Kuretase antara Pemberian Lidokain Paraservikal dan Intraservikal - Yudhistya Ngudi Insan Ksyatria; Heru Pradjatmo; Ova Emilia (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Curettage is a gynecological diagnostic and therapeutic procedures. Curettage actions causing sensation of pain although the pain threshold is different for each person. Local anesthesia is an effective choice for various minor gynecological procedures. One of them is paracervical block. Paracervical block reduces pain by blocking nerve impulses across the uterovaginal plexus. Another method is the injection of local anesthetic trough intracervical who works as an anesthetic infiltrating agent, distending the tissue, causing mechanical disruption of nerve impulses. Theoritically, intracervical lidocaine injection will require a lower level of precision than the blockade of peripheral nerves directly, more reliable and reproducible. We measured patient’s pain during curettage usingthe Visual Analogue Scale (VAS). Method: RCT Location of study: Bantul District Hospital, Wonosari District Hospital, and Banjarnegara Distric Hospital. Result and Discussion: The study included 60 patients who got curettage within inclusion criteria. Every time patients came, we performed randomization and divided the patients into two groups, the control group (paracervical) and intervention group (intracervical), 30 subjects each. VAS was measured 5 minute after curettage was started. Characteristics of subjects in curettage frequency, curettage indication, parity and educational level for both groups are equal, did not differ statistically. The results of the mean pain scale (VAS). In the control group was 42,33±16,583 and 34,33±18,880 on the treatment group. Mean difference was 8 mm, with 95% CI -1.124 to 17.124 and p=0.408. The difference was not significant statistically. The intracervical group has mild pain scale (VAS<44 mm) in 27 of 30 patient, compared to 15 of 30 patients in paracervical group. It result in Relative Risk (RR) of 1,532. Conclusion: Intracervical lidocaine injection can be considered as an alternative local anesthetic on curettage. The average pain scale did not differ significantly with paracervical block. And both of it located in VAS < 44mm (mild pain). Intracervical lidocaine injection even have RR= 1,532 compared with paracervical block to produce mild pain scale (VAS < 44 mm). Keywords: curettage; paracervical;intracervical ;VAS